Book Review: Piot, Charles, ed. 2016: Doing Development in West Africa: A Reader by and for Undergraduates. (April 2018) - Byers, Madeline
Piot, Charles, ed. 2016: Doing Development in West Africa: A Reader by and for Undergraduates . Durham and London: Duke University Press. v + 216 pp. 84.95 (clothbound), 23.95 (paperback). ISBN: 9780822361763 (clothbound), 1923 (paperback).